Extended‐spectrum β‐lactamase producing Klebsiella spp. in chicken meat and humans: a comparison of typing methods. (19th August 2013) - Overdevest, I. T. M. A.; Heck, M.; van der, K.; Huijsdens, X.; van, M.; Rijnsburger, M.; Eustace, A.; Xu, L.; Hawkey, P.; Savelkoul, P.; Vandenbroucke‐Grauls, C.; Willemsen, I.; et al.
Abstract Recently, chicken meat was identified as a plausible source of extended‐spectrum β‐lactamase (ESBL) ‐producing Escherichia coli in humans. We investigated the relatedness of ESBL‐producing Klebsiella spp. in chicken meat and humans. Furthermore, we tested the performance of SpectraCell RA® (River Diagnostics), a new typing method based on Raman spectroscopy, in comparison with multilocus sequence typing (MLST) for Klebsiella pneumoniae. Twenty‐seven phenotypically and genotypically confirmed ESBL‐producing Klebsiella spp. isolates were typed with MLST and SpectraCell RA. The isolates derived from chicken meat, human rectal swabs and clinical blood cultures. In the 22 ESBL‐producing K. pneumoniae isolates, CTX‐M15 was the predominant genotype, found in five isolates of human origin and in one chicken meat isolate. With MLST, 16 different STs were found, including five new STs. Comparing the results of SpectraCell RA with MLST, we found a sensitivity of 70.0% and a specificity of 81.8% for the new SpectraCell RA typing method. Therefore, we conclude that SpectraCell RA is not a suitable typing method when evaluating relationships of ESBL‐producing Klebsiella spp. at the population level. Although no clustering was found with isolates of chicken meat and human origin containing the same ESBL genes, MLST showed no clustering into distinctive clones of isolates from chicken meat and human origin. More studies are needed to elucidate the role of chicken meat in the rise of ESBL‐producing Klebsiella spp. in humans.